Agricultural soils as a sink to mitigate CO2 emissions - Paustian, Keith; Andren, O.; Janzen, H.H.; Lal, R.; Smith, P.; Tian, G.; Tiessen, H.; Noordwijk, M. van; Woomer, P.L. (Wiley, 1997)
Agricultural soils, having been depleted of much of their native carbon stocks, have a significant CO2 sink capacity. Global estimates of this sink capacity are in the order of 20-30 Pg C over the next 50-100 years .Management practices to build up soil C must increase the input of organic matter to soil and/or decrease soil organic matter decomposition rates. The most appropriate management practices to increase soil C vary regionally dependent on both environmental and socioeconomic factors